Methanotrophy: A Biological Method to Mitigate Global Methane Emission - Anju Rani; Aarushi Pundir; Medhashree Verma; Samiksha Joshi; Geeta Verma; Snežana Andjelković; Snežana Babić; Jasmina Milenković; Debasis Mitra (Microbiology Research, 2024)
Methanotrophy is a biological process that effectively reduces global methane emissions by utilizing microorganisms that can utilize methane as a source of energy under both oxic and anoxic conditions, using a variety of different electron acceptors. Methanotrophic microbes, which utilize methane as their primary source of carbon and energy, are microorganisms found in various environments, such as soil, sediments, freshwater, and marine ecosystems. These microbes play a significant role in the global carbon cycle by consuming methane, a potent greenhouse gas, and converting it into carbon dioxide, which is less harmful. However, methane is known to be the primary contributor to ozone formation and is considered a major greenhouse gas. Methane alone contributes to 30% of global warming; its emissions increased by over 32% over the last three decades and thus affect humans, animals, and vegetation adversely. There are different sources of methane emissions, like agricultural activities, wastewater management, landfills, coal mining, wetlands, and certain industrial processes. In view of the adverse effects of methane, urgent measures are required to reduce emissions. Methanotrophs have attracted attention as multifunctional bacteria with potential applications in biological methane mitigation and environmental bioremediation. Methanotrophs utilize methane as a carbon and energy source and play significant roles in biogeochemical cycles by oxidizing methane, which is coupled to the reduction of various electron acceptors. Methanotrophy, a natural process that converts methane into carbon dioxide, presents a promising solution to mitigate global methane emissions and reduce their impact on climate change. Nonetheless, additional research is necessary to enhance and expand these approaches for extensive use. In this review, we summarize the key sources of methane, mitigation strategies, microbial aspects, and the application of methanotrophs in global methane sinks with increasing anthropogenic methane emissions.